FRANCHISE AGREEMENTS AS COMPONENTS OF INTERNATIONAL TRADE - Атаманчук, З.; Адаменко, М.; Нестерчук, Н.В. (SWorldJournal, 2023)
Today, franchising is recognized in the world as the most progressive form of business. The advantages of franchising are beneficial to novice entrepreneurs, as it significantly reduces the risk of failure and loss of funds. Franchising is beneficial for